2017
DOI: 10.1186/s12014-017-9140-6
|View full text |Cite
|
Sign up to set email alerts
|

A new enzyme-linked immunosorbent assay (ELISA) for human free and bound kallikrein 9

Abstract: BackgroundKallikrein 9 (KLK9) is a member of the human kallikrein-related peptidases family, whose physiological role and implications in disease processes remain unclear. The active form of the enzyme is predicted to have chymotryptic activity. In the present study, we produced for the first time the active recombinant protein and monoclonal antibodies, and developed novel immunoassays for the quantification of free and bound KLK9 in biological samples.MethodsThe coding sequence of mature KLK9 isoform (mat-KL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… Type of cancer Type of biomarker Method of detection/Targeted Biomarkers/Ref. Ovarian Amino acids Immunocapture/parallel reaction monitoring mass spectrometry - mat-KLK9 ( Filippou et al, 2017 ) Lung Metabolites Qualitative tandem liquid chromatography quadrupole time of flight mass spectrometry - Suberic acid, tetrahexose, trihexose, nonanedioic acid & monoglyceride ( Calderón-Santiago et al, 2015 ) Lung, Gastric, Prostate, Head, Kidney, pancreas Chiral alcohol Gas chromatography with mass spectrometry - 2-ethyl-1-hexanol, hexanal, octanal & 2,6 dimethyl-7-octen-2-ol ( Monedeiro et al, 2020a ) Head and Neck Metabolites Headspace solid-phase micro extraction (SPME) gas chromatography (GC) mass spectrometry (MS) – 81 VOMs as potential tumor markers ( Opitz and Herbarth, 2018 ) Prostate Amino acids Mass spectrometry – KLK4 ( Karakosta et al, 2016 ) Various Nucleic acids Real-time RT-PCR - DCD ( Sakurada et al, 2010 ) …”
Section: Liquid Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“… Type of cancer Type of biomarker Method of detection/Targeted Biomarkers/Ref. Ovarian Amino acids Immunocapture/parallel reaction monitoring mass spectrometry - mat-KLK9 ( Filippou et al, 2017 ) Lung Metabolites Qualitative tandem liquid chromatography quadrupole time of flight mass spectrometry - Suberic acid, tetrahexose, trihexose, nonanedioic acid & monoglyceride ( Calderón-Santiago et al, 2015 ) Lung, Gastric, Prostate, Head, Kidney, pancreas Chiral alcohol Gas chromatography with mass spectrometry - 2-ethyl-1-hexanol, hexanal, octanal & 2,6 dimethyl-7-octen-2-ol ( Monedeiro et al, 2020a ) Head and Neck Metabolites Headspace solid-phase micro extraction (SPME) gas chromatography (GC) mass spectrometry (MS) – 81 VOMs as potential tumor markers ( Opitz and Herbarth, 2018 ) Prostate Amino acids Mass spectrometry – KLK4 ( Karakosta et al, 2016 ) Various Nucleic acids Real-time RT-PCR - DCD ( Sakurada et al, 2010 ) …”
Section: Liquid Biopsymentioning
confidence: 99%
“…The authors found that in all cases, KLK9 concentration in sweat was stable after 24 h. At RT, on day seven, the concentration decreased by about 40%. KLK9 spiked in serum, instead, decreased by about 60% after 24 h incubation and this was attributed to the formation of heterocomplexes with endogenous serine protease inhibitors ( Filippou et al, 2017 ).…”
Section: Liquid Biopsymentioning
confidence: 99%
“…Tissue cytosolic extracts were prepared from snap-frozen tissues as previously described [24]. Briefly, fresh frozen human tissues were pulverized to a fine powder in 0.2 g/ml of extraction buffer.…”
Section: Tissue Extract Preparationmentioning
confidence: 99%
“…Proteases are associated with most biological processes because of their ability to regulate the physiological functions of proteins via hydrolysis. Because its aberrant activity plays a crucial role in a variety of diseases, including cardiovascular and inflammatory diseases as well as cancer, the detection of proteases is of great importance for diagnosis and medical treatment. Typically, protease detection is achieved by specificity-based assays, such as enzyme-catalyzed reactions , and enzyme-linked immunosorbent assays (ELISAs) based on antigen–antibody reactions. However, the development of highly specific recognition remains difficult, and the design/production of antibodies or enzyme substrates for binding or reaction visualization are costly and laborious.…”
Section: Introductionmentioning
confidence: 99%